Foundations of sensation and perception - Mather, George; Mather, George (Hove, East Sussex [England] ; New York : Psychology Press, 2009)
"The first edition of this comprehensive introduction to sensation and perception has been highly praised for its unique approach: it allows students to thoroughly grasp the fundamental principles in relation to the relatively simple sensory systems before moving on to the more complex topics."--BOOK JACKET.
General principles -- Classification of the senses -- Methods used to study perception -- General principles of sensation and perception -- The chemical senses -- Smell -- Taste -- Flavor -- Evaluation -- The body senses -- The somatosensory system -- The vestibular system -- The physics and biology of audition -- Sound as a physical stimulus -- The physiology of the auditory system -- Perception of sound -- Loudness perception -- Pitch perception -- Auditory localization -- Speech perception -- Auditory scene analysis -- Hearing dysfunction -- The physics of vision--light and the eye -- What is light? -- Some important properties of light -- The eye -- Visual physiology -- The retina -- The visual pathway -- The visual cortex -- Spatial vision -- Fundamental functions -- Representaion at multiple spatial scales -- Uses of spatial filters -- Shape and object perception -- Introduction: The three stage model -- Shape representation -- Object representation -- Scene perception -- Depth perception -- The multiplicity of depth cues -- Cue combination -- Visual motion perception -- Detecting movement -- The integration of motion detector responses -- Multiple processes in motion perception -- Color vision -- Color space -- Color mixture -- Dual-process theory -- Color interactions -- Color deficiency -- Multisensory processing in perception -- Multisensory processing -- Synesthesia -- Individual differences in perception -- Age -- Sex -- Culture -- Expertise -- Idiosyncratic individual differences.
Rev. ed.: Foundations of perception. 2005.
Includes bibliographical references (p. [421]-439) and indexes.
Keywords: Perception